2020
DOI: 10.1093/heapro/daaa089
|View full text |Cite
|
Sign up to set email alerts
|

Exploring health literacy and its associated factors among Palestinian university students: a cross-sectional study

Abstract: Summary Health literacy plays an important role in personal and community health. Since university is a turning point when young adults begin to take responsibility for their own health, understanding university students’ health literacy levels is crucial. To this end, we aimed to explore health literacy and its associated factors among Palestinian university students. We conducted a cross-sectional study at Birzeit University in the Ramallah district. We recruited 472 students using convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 45 publications
4
28
3
2
Order By: Relevance
“…Contrary to our expectation, health literacy was not associated with the academic year and parent's highest level of education as reported in previous studies [7,8,14,17,33]. This absence of association is not well understood and needs to be explored prospectively in future research.…”
Section: Plos Global Public Healthcontrasting
confidence: 99%
“…Contrary to our expectation, health literacy was not associated with the academic year and parent's highest level of education as reported in previous studies [7,8,14,17,33]. This absence of association is not well understood and needs to be explored prospectively in future research.…”
Section: Plos Global Public Healthcontrasting
confidence: 99%
“…11,12,14,17 In the contrary, health literacy was not associated with parent's highest level of education as reported in previous studies. 11,14,[18][19][20] This contrast observation is not well understood and needs to be explored prospectively in future research. Moreover, who did not have any family history of NCDs found to have less literacy on NCDs prevention.…”
Section: Discussionmentioning
confidence: 97%
“…The finding coincides with the Palestinian university-based study which revealed that more frequent use of health services is associated with higher health literacy. 20 Likewise, study in Taiwan showed a positive association between e-health literacy and health service utilization among college students. 21 As solutions, proper establishment of health insurance as well as frequent medical checkups, either from illness or as screening, could lead to more exposure to health professionals, which might contribute to higher health literacy among university students.…”
Section: Discussionmentioning
confidence: 99%
“…S. ÇELİK, Z. İSTEK, A. KIZKIN, M. C. YİĞİT, H. KAÇAN Güzel 20 , Okur ve arkadaşları 17 ile Sarhan ve arkadaşları 31 çalışmalarında öğrencilerin gelir düzeyinin sağlık okuryazarlık düzeylerini etkilemediğini bildirirken, Zhang ve arkadaşları 29 öğrencilerin sosyoekonomik durumları sağlık okuryazarlık düzeyleri arasında ilişki olduğunu rapor etmiştir. Şirin ve arkadaşları da ailenin ekonomik durumu arttıkça öğrencilerin sağlık okuryazarlık düzeyinin mükemmel düzeye ulaştığını belirtmiştir.…”
Section: Sonuç Ve öNerilerunclassified
“…Annesi okuryazar olmayan öğrencilerin sağlık okuryazarlığı puan ortalaması anlamlı şekilde en düşüktü (p<0,05). Şirin ve arkadaşları 22 ile Sarhan ve arkadaşları 31 da anneleri okuryazar olmayan öğrencilerin sağlık okuryazarlığı puan ortalamalarının en düşük olduğunu saptamışlardır. Zhang ve arkadaşları, en yüksek eğitim düzeyine sahip ebeveynlerin öğrencilerin sağlık okuryazarlık düzeylerini anlamlı şekilde olumlu etkilediğini bildirmiştir 29 .…”
Section: Sonuç Ve öNerilerunclassified